Frequency of Diabetic Foot Ulcer in Patients with Diabetes Mellitus: A Study at Saint Francis Referral Hospital, Morogoro-Tanzania - Karuhanga, Theresia A.; Thomas, Claus; Madoshi, Philbert; Balthazary, Sakurani T (Achievements and Challenges of Medicine and Medical Science Vol. 8, 2024)
Introduction: Diabetic foot ulcer is a common complication of Diabetic mellitus. Uncontrolled hyperglycemia leads to diabetic foot ulcers (DFU), which eventually results in amputation. Prevention and management of DFU requires a multi-disciplinary to improve DFU care. Methodology: The study was conducted at St. Francis Referral Hospital a semi-urban health institute in the southwestern part of Tanzania. A cross-section retrospective study was conducted at Saint involving the hospital information of the patients who had foot ulceration. Data were analyzed by using the Statistical Package for Social Sciences (SPSS version 26). Results: During the 12 months, DFU admission was found to be 19.14%. The 5th decade was the predominant age group which is 32.0% and the 9th decade was the least of all. There was a relatively high mortality rate (15.1%). The most identified factor for unfavorable outcomes was the presence of infection and severity of wound whose both P-values were statistically significant (0.010 and 0,027 respectively). Conclusion: There is a need for diabetic foot care improvement involving reversed clinical patient visits in remote rather than the patients attending hospitals. The management and designing of this protocol should be in a multidisciplinary approach, involving surgeons, physicians, physiotherapists, nutritionists as well as nurses at the hospital level. Emphasis should be on proper assessment and grading of the ulcer severity to enable DFU prevention and proper management.